GROWTH OF Caulerpa sp. IN THE CULTIVATION OF BASIC PATCH SYSTEM IN ROMPO VILLAGE, LANGGUDU DISTRICT - Apriliyanti, Fisma Josara; Cokrowati, Nunik; Diniarti, Nanda (Jurnal Media Akuakultur Indonesia, 2021)
Caulerpa sp. is a type of sea grape from the green algae group that can be used as food. In Indonesia there are still very few people who can cultivate it and its current availability comes from harvesting it in nature. The aim of this research was to analyze the effect of different seed weights on the growth and antioxidant content of Caulerpa sp. cultivated using the basic stake method. The research was carried out in Rompo Village, Langgudu District, Bima Regency. Cultivation of Caulerpa sp. carried out for 30 days. The research used the Completely Randomized Design (CRD) method which consisted of 5 treatments, namely; A : 100 grams (20 g / 5 points), B : 125 grams (25 g / 5 points), C : 150 grams (30 g / 5 points), D : 175 grams (35 g / 5 points), and E : 200 grams (40 g / 5 points). The research results explained that the highest absolute growth was in treatment E (69.8 grams). The highest specific growth was in treatment A (1.395% / day). Number of dots of Caulerpa sp. The most were found in treatment E (414 dots). Antioxidant value of Caulerpa sp. The highest was in treatment A (87.15%). The conclusion of this research is that different seed weights have an influence on absolute, relative growth, number of dots and antioxidant content. A seedling weight of 200 grams (Treatment E) gave the best absolute growth and increase in the number of dots, namely 69.8 grams and 414 dots. A seed weight of 100 grams (A) provides the best specific growth and amount of antioxidants, namely 1.395% / day and 87.15%.